Price volatility measures in Chinese emissions trading pilots: fine tuning or fiddling while carbon burns?. Issue 3 (December 2016) - Geroe, Steven
Abstract : This paper considers the nature and role of measures in China's Emissions Trading Scheme (ETS) pilots specifically designed to constrain market price fluctuation. These are primarily banking and borrowing of credits, permit reserves combined with direct market intervention, variations of trading bands/corridors, price ceilings and floors, market 'safety valves' and adjustment of emissions caps in defined circumstances. To provide realistic context, the setting of emissions caps, methods to allocate permits and the broad range of other factors impacting on Chinese ETS prices are considered. Key aspects of the market performance of the Chinese ETS pilots, focusing on price levels and volatility, are then addressed. It is argued that elements of scheme design regarding emissions cap setting and allocation of permits have the most fundamental impact on price levels. Compliance measures, rules regarding international investment and secondary markets and transitional provisions from the pilots to a national ETS have also been significant. Price volatility measures can nonetheless play a significant role in providing adequate price stability to moderate investment uncertainty. Price floors and ceilings can also play a role in incentivizing investment, to implement emissions reduction goals. To be effective, however, scheme design needs to demonstrate a credible commitment to scarcity of permits through adequately ambitious emissions caps and allocation methods.